An Educational Interventional Programme for Prevention and Management of Needle Stick Injuries Among Nursing Students at A Tertiary Care Hospital, Jabalpur, Madhya Pradesh - Trivedi, Anshuli; Kasar, Pradeep Kumar; Tiwari, Rajesh; Verma, Prashant; Sharma, Arvind (National Journal of Community Medicine, 2013)
Background: Nursing students are at increased risk of acquiring blood borne infections, this is largely due to NSI which they encounter in there every day work. They are frequently unaware of prevention and management of NSI and proper BMW disposal. Objective: To assess and enhance knowledge of nursing students for prevention and management of NSI . Methods: This was a Quasi experiment study conducted at Nursing College, NSCB Medical College Jabalpur (M.P.) among 100 nursing students. A preformed questionnaire was used to assess existing knowledge of prevention and management of NSI, then students were given series of lectures and interactive sessions to prevent and manage NSI then same group was subjected to post intervention assessment. Results: It was observed that 78% respondents suffered NSI was during recapping of needle. Other than needle,86% respondents mentioned of getting struck by stylet of IV catheter, 14% subjects recalled more than 5 incidences of NSI in past 15 days. In post intervention assessment it was observed that intervention made a significant (Wilcoxon signed rank Test Z=6.68,p<0.001)) impact in knowledge of students for prevention and management of NSI. The intervention motivated 5 more students for Hepatitis B immunization. Conclusions: Sensitization of nursing students for prevention and management of NSI is quintessential in preventing these occupational hazards and should be included in nursing training curriculum.